(untitled) (Bangladesh Agronomy Journal, 2022)
The experiment was conducted at farmer’s field of Kapasia, Gazipur during November, 2011 to March, 2013under the AEZ 28 (Modhupur Tract).The experiment was carried out to find the effects of varieties and planting dates on growth, yield and quality of sugarcane. Two varieties (viz; Isd 38 and Isd 39) and five planting datesfrommid-November to mid-Marchwere laid out in a Factorial Randomized Complete Block (RCB) design with three replications. Among the varieties, there was no significant difference; however Isd 38 performed better than Isd 39 in all aspect of yield contributing characters. Growth characters viz., tillers and millable cane stalks were significantly influenced by different planting dates. The highest germination (72.17%), tiller (111.03×103 ha-1), millable cane (91.12×103 ha-1), pol % cane (14.91%)and cane yield (75.47 t ha-1) were obtained from mid- November planting and gradually decreased with the advancement of planting times where all the lowest values were recorded from mid-March planting. Interaction between variety and planting date, mid-November planting with Isd 38 produced the highest germination (73.67%), tiller (115.39 ×103 ha-1), millable cane (98.16 ×103 ha-1), pol % cane (14.95%) and cane yield (93.64 t ha-1). The overall results revealed that variety Isd 38 in mid-November planting is optimum for sugarcane production under the Modhupur tract soils of Bangladesh. Bangladesh Agron. J. 2021, 24(2): 73-81